Analyse De La Capacité De L’Etat Burundais à Répondre Aux Besoins Fondamentaux de la population: Cas De L’eau Et De La Santé - Alexis, Ndabarushimana (European Scientific Journal, ESJ, 2018)
Access to water and health care is one of the basic needs of the human being. This study conducted with 96 individuals selected using Alain BOUCHARD’s technic highlights the state of play on the capacity of the State of Burundi to meet the basic needs of the population in the water and health sectors. The study also shows the level of satisfaction of public service users in these sectors. The respondents were distributed in 26 localities in 8 provinces of Burundi. The results of this research shows that Burundi is still unable to effectively meet the needs of the population in the water and health sectors. And this despite the implementation of the policy of free health care for pregnant women and children under 5 years since 2006. Only 51.15% say they are satisfied by the health services offered. The environmental sanitation and drinking water supply had been integrated into the Minimum Care Package (MSP), but the results obtained in this study show that the road ahead is still long. Only 7.8% of respondents are very satisfied in urban areas while in rural areas 12.6% are very satisfied. The satisfaction rate is 70.92% in urban areas compared to 45.04% in rural areas. In urban areas, 21.28% are not satisfied compared to 42.36% in rural areas.